Rancang Bangun Aplikasi Tes Kesegaran Jasmani Berbasis Android - Amzah, Ridho Al; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Implementation of Physical Freshness Test today is done manually which makes the executive officer TKJI have difficulties in calculating the results of the test participants. TKJI application is an application used to facilitate TKJI officers in carrying out tests Physical Freshness. TKJI application used for participants aged 16-19 years based on Android. There are five criteria were used that test run Sprint 60 Meter, Test Suspension Lift Body, Baring Test Sitting, Upright Skip Test, Test Medium 1200 Meter Sprint. Usability Testing Results of this study of 20 respondents with 19 questions obtained results revealed 90.25% Very Worthy. The purpose of this research is to develop software applications Physical Freshness Android-Based Test to assist in the implementation and measurement of results TKJI. Keywords – Physical Fitness Test; Android application; Usability Testing; TKJI Result Measurement